Energy Efficiency of Transport Sector in Bulgaria: analysis and Assessment of Key Indices and Trends - Nikolova, Hristina; Minkov, Tashko (Research Papers, 2014)
Transport energy efficiency is now very close to the top of the political agenda in many countries. There is a widespread consensus that progress towards sustainable development is essential. However, there is considerable debate as to what this term means? One particular part of this debate concerns the role of transport as a major consumer of energy and a generator of pollution. The question is: can transport activity be planned and managed in such a way as to be more energy-efficient?This paper aims to explore the importance of transport energy efficiency for economic development of the country. It analyses different indicators and measures with particular emphasis on the energy consumption. The various paragraphs of this paper concentrate on the real problems which energy efficiency of transport present to policy-makers and assess the contribution that the analysis can make to handling more effectively respective considerations in transport decision making. The conclusion of the paper is aimed to provide a general background against which the new research may be set.
Keywords: Energy consumption of transport; Sustainable transport development; Energy efficiency; Economic crises